Electronically tunable compact inductance simulator with experimental verification - Bhardwaj, Kapil; Srivastava, Mayank; Kumar, Anand; Singh, Ramendra; Tangsrirat, Worapong (My University, 2024)
A novel inductance simulation circuit employing only two dual-output voltage-differencing buffered amplifiers (DO-VDBAs) and a single capacitance (grounded) is proposed in this paper. The reported configuration is a purely resistor-less realization that provides electronically controllable realized inductance through biasing quantities of DO-VDBAs and does not rely on any constraints related to matched values of parameters. This structure exhibits excellent behavior under the influence of tracking errors in DO-VDBAs and does not exhibit instability at high frequencies. The simple and compact metal-oxide semiconductor (MOS) implementation of the DO-VDBAs (eight MOS per DO-VDBA) and adoption of grounded capacitance make the proposed circuit suitable for on-chip realization from the perspective of chip area consumption. The function of the pure grounded inductance is validated through high pass/bandpass filtering applications. To test the proposed design, simulations were performed in the PSPICE environment. Experimental validation was also conducted using the integrated circuit CA3080 and operational amplifier LF-356.
Keywords: CA3080; CMOS; DO-VDBA; electronic tunability; inductor